Benign form of multiple sclerosis: MRI evidence for less frequent and less inflammatory disease activity. Issue 9 (September 1994) - Kidd, D; Thompson, A J; Kendall, B E; Miller, D H; McDonald, W I
Abstract : Data from two serial studies comparing the MRI activity of two groups of 11 patients, one with early relapsing-remitting (mean disease duration 3.5 years), the other benign (mean disease duration 22 years) multiple sclerosis are presented. Those with benign disease developed fewer new or enlarging lesions, and such lesions that occurred had a lower incidence of gadolinium enhancement, a marker of inflammation. These results, when considered in conjunction with other published studies, suggest that both the frequency of new lesions and the amount of inflammation within them influence the development of disability in multiple sclerosis.